ANATOLIAN KINGS OF GALATIAN ORIGIN: AMINYNTAS AND AFTER HIM - Kevser TAŞDÖNER (Fırat University, 2019)
Galatians (or Celts), who came to Anatolia via straits in 278/277 BC, was a tribe of Central Europe origin. The reason why they wanted to come to Anatolia was looting. They looted coastal regions of the Aegean Sea of Anatolia for about 10 years. Then, they settled down in Phrygia (Galatia) which they named after themselves. Ankyra (Ankara) and Tavion (Küçüknefes Köy) became the most important residential areas of Galatians. Until the first century BC before setting up a kingdom, they preserved their traditional way of life in three big tribes (Tektosags, Tromeks,and Tolistobogis). No Galatian ruler claimed ‘king’ title by the end of the third Mithridates War. In the end of this war, Deiotoros, who was a Galatian leader (regulus or tetrarkhes), was given ‘king’ title by the Roman statesman and general Pompeius. Then, Romans continued to appoint kings of Galatian origin. The purpose of this article is to mention kings of Galatian origin, who were appointed by Romans as dependant kings, to discuss the reasons why Romans preferred them as well as the question where Galatians governed.